2013
DOI: 10.1182/blood.v122.21.4052.4052
|View full text |Cite
|
Sign up to set email alerts
|

KIT D816V Mutation Burden Predicts Prognosis and Survival In Patients With Mastocytosis and Correlates With The WHO Type Of The Disease

Abstract: Mastocytosis is characterized by abnormal expansion and accumulation of neoplastic mast cells in one or more organ systems. Traditionally, mastocytosis is divided into cutaneous mastocytosis (CM) and systemic mastocytosis (SM). In most patients with SM, the transforming somatic mutation KIT D816V is detected. However, only few studies have quantified the KIT D816V allele burden in CM and SM. The aim of the present study was to quantify KIT D816V in various forms of mastocytosis and to correlate the allele burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 0 publications
4
37
0
Order By: Relevance
“…In the present study, the KIT D816V allele burden was not significantly higher in SM patients who fulfilled the major criterion compared to patients who did not. This result is in line with a previous result by Hoermann et al (2014) who observed no significant correlation between the KIT D816V allele burden and the percentage of MCs in the BM biopsy or BM smear . Together, these results indicate that the association between the allele burden and degree of MC infiltration in the BM is limited, likely because the allele burden also reflects the degree of non‐MC lineage involvement in addition to the neoplastic MC burden .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the KIT D816V allele burden was not significantly higher in SM patients who fulfilled the major criterion compared to patients who did not. This result is in line with a previous result by Hoermann et al (2014) who observed no significant correlation between the KIT D816V allele burden and the percentage of MCs in the BM biopsy or BM smear . Together, these results indicate that the association between the allele burden and degree of MC infiltration in the BM is limited, likely because the allele burden also reflects the degree of non‐MC lineage involvement in addition to the neoplastic MC burden .…”
Section: Discussionsupporting
confidence: 92%
“…We have previously demonstrated that the vast majority (94%) of already diagnosed SM patients test KIT D816V mutation positive in blood when using a sufficiently sensitive method . However, in line with similar studies from other groups also detecting the KIT D816V mutation in blood in high numbers of SM patients, our previous study was primarily based on blood samples obtained at, or later than, the time of the BM investigation. These blood samples were not used in the diagnostic workup to guide the BM biopsy, but were instead sampled after the decision to perform a BM biopsy was made (at the day of the BM biopsy or after the SM diagnosis was established).…”
Section: Discussionmentioning
confidence: 68%
“…In parallel with the above findings, recent studies have demonstrated that most ISM patients, including the majority of ISMs− cases, show KIT ‐mutated cells in PB, even in the absence of multilineage BM involvement of hematopoiesis by the KIT mutation. Nevertheless, no study has investigated so far the specific compartment of circulating PB cells that carries the KIT mutation, particularly at the earliest disease stages.…”
Section: Introductionsupporting
confidence: 63%
“…There are several published algorithms to assist in the diagnostic approach and determine which adults are more likely to have systemic disease (Alvarez-Twose et al, 2010;Gulen et al, 2014;Carter et al, 2018). Recent studies identifying and quantitating the KIT D816V mutation in peripheral blood (PB) in adults have suggested it to be a valuable tool for diagnosis, (Kristensen et al, 2011(Kristensen et al, , 2014Jara-Acevedo et al, 2015) to determine disease burden and monitoring (Erben et al, 2014), and to assess response to therapy (Hoermann et al, 2014). In adults, the KIT D816V allelic burden in PB correlates with serum tryptase (Kristensen et al, 2013;Erben et al, 2014;Hoermann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identifying and quantitating the KIT D816V mutation in peripheral blood (PB) in adults have suggested it to be a valuable tool for diagnosis, (Kristensen et al, 2011(Kristensen et al, , 2014Jara-Acevedo et al, 2015) to determine disease burden and monitoring (Erben et al, 2014), and to assess response to therapy (Hoermann et al, 2014). In adults, the KIT D816V allelic burden in PB correlates with serum tryptase (Kristensen et al, 2013;Erben et al, 2014;Hoermann et al, 2014). However, the diagnosis of systemic disease in children remains a challenge because, outside of the clinical finding of organomegaly, which correlates with systemic disease, surrogate markers to help identify those children where a marrow examination might be warranted to establish systemic disease, are lacking (Carter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%